Development and Validation of a Phenotyping Computational Workflow to Predict the Biomass Yield of a Large Perennial Ryegrass Breeding Field Trial - Gebremedhin, Alem; Badenhorst, Pieter; Wang, Junping; Shi, Fan; Breen, Ed; Giri, Khageswor; Spangenberg, German C.; Smith, Kevin (Frontiers in Plant Science, 2020)
Increasing dry matter yield is the most important objective in perennial ryegrass breeding program. Current yield assessment methods are time-consuming and subjective. These assessments involve multiple measurements and selection procedures across seasons and years to evaluate biomass yield repeatedly. This contributes to the slow process of new cultivar development and commercialisation. This study developed and validated a computational phenotyping workflow for image acquisition, processing and analysis of spaced planted ryegrass and investigated sensor-based dry matter yield (DMY) yield estimation of individual plants through normalised difference vegetative index (NDVI) and ultrasonic plant height data extraction. The DMY of 48,000 individual plants representing fifty advanced breeding lines and commercial cultivars was accurately estimated at multiple harvests across the growing season. NDVI, plant height and predicted DMY obtained from aerial and ground-based sensors illustrated the variation within and between cultivars across different seasons. Combining NDVI and plant height of individual plants was a robust method to enable high-throughput phenotyping of biomass yield in ryegrass breeding. Similarly, the plot-level model indicated good to high-correlation between the predicted and measured DMY across three seasons with R² between 0.19- 0.81 and root mean square errors (RMSE) values ranging from 0.09-0.21 kg/plot. The model was further validated using a combined regression of the three seasons harvests. This study further sets a foundation for the application of sensor technologies combined with genomic studies that lead to greater rates of genetic gain in perennial ryegrass biomass yield.